OP105 Factors Affecting Horizon Scanning For Hospital-Based Health Technology Assessment. (2019) - Chalkidou, Anastasia; Erskine, Jamie; Macmillan, Thomas; Keevil, Stephen
Abstract : Introduction: The strategic MedTech investment for the expansion of a central London paediatric hospital must sustain its ambitions to remain a state-of-the-art hospital, whilst implementing recent and future MedTech innovations and taking into account spatial and financial limitations. Horizon scanning (HS) is an important health technology assessment (HTA) tool to achieve these goals. To this end, we developed a methodology to help decide the suitability of investing in the following imaging-based MedTech: a hybrid theatre incorporating a biplane, intra-operative MRI (iMRI), multi-detector computed tomography (CT) scanners, and an EOS imaging system and predict the complementary technologies required for the decade to come. These technologies not only require adequate spatial resources but a significant upfront capital investment. Methods: Three sources of information were used: i) a literature search, selected journals and other horizon scanning resources that examined current efficiency, safety, and cost-effectiveness for the proposed technologies, ii) expert elicitation in the form of user-group meetings and one-to-one discussions with clinical and service management teams and iii) hospital data consisting of audit and information from capital equipment bids. Results: With the exception of limited comparative data on iMRI (mainly including adults), little evidence exists to support investment in the proposed technologies. However, the decision of whether to adopt these technologies was influenced not only by existing evidence on the proposed technologies and associated cost but other factors such as local disease burdens, hospital staff requirements (training, expertise), space requirements for the new MedTech, and its impact on organizing healthcare services and hospital workflows. Complementary technologies associated with radiation monitoring image visualization and control were identified. Conclusions: Strategic MedTech investment requires a holistic approach that assigns equal weight to information arising by expert elicitation and hospital audit data with existing literature evidence. The decision for adoption is heavily influenced by the clinical expertise and hospital workflows.